Informal Economic Activities of the Elderly in Pekanbaru City - Sinambela, Yefty Feniester; Asriwandari, Hesti (CV. Rayyan Dwi Bharata, 2024)
This study aims to determine informal economic activities carried out by the elderly in the city of Pekanbaru who are still working and find out the reasons behind the elderly are still actively working based on social actions. This study used descriptive qualitative research methods in data collection using observation, interview, in-depth and documentation techniques. The subjects in this study amounted to seven people, of which five elderly people were actively working, including banana fruit traders, tissue sellers, blacksmiths, parking attendants, seasoning entrepreneurs, and two supporting subjects, namely children of the elderly and the Head of protection and social security. This study used purposive techniques based on certain criteria. The results of this study show that in carrying out economic activities, preparation is needed before carrying out activities, the process of implementing activities and the difficulties experienced during work. The results of observational analysis of research show that in carrying out economic activities in the need for behavior and physical ability to work by showing interest in work and social action. Rational and irrational social actions are behind the elderly still working. Instrumental actions go into all the reasons they work because the economic activity they do certainly produces something useful for their purposes, although these actions are not the main reason they work. The informal economic activities that the elderly choose are carried out independently. Independent means independent in the funds spent, independent in energy and able to overcome difficulties on their own without anyone protecting them.